Prediksi Ancaman Keamanan dan Antisipasinya Pada Pemilu Serentak 2024 - Ade Mulya (Journal of Research and Development on Public Policy, 2023)
ABSTRACT: The aim of the article is to provide a prediction of the threat of simultaneous elections in 2024 by highlighting the threat of absenteeism or white groups, the threat of delays in election logistics, the threat of identity politics, the threat of successful team conflict, and the threat of security disturbances. The method used is a literature review from secondary sources related to threat prediction and anticipation. The findings in this article show that the readiness and cooperation of election organizers, the police and political parties is very important to reduce and manage threats from the beginning to the end of the 2024 simultaneous elections.